Gaps in Heat-Related Knowledge, Practices and Adaptation Strategies Among Coaches in German Outdoor Sports - Sophie Leer; Zoe A. Parsons; Sven Schneider (International Journal of Public Health, 2024)
ObjectivesClimate change is increasing the risk of heat-related illness in outdoor sports. Coaches have a responsibility to protect the athletes in their care. In this study, the knowledge and practice of German coaches in heat prevention were evaluated nationwide.MethodsCoaches (n = 1,200) from the ten largest outdoor sports in Germany were asked about their knowledge using the knowledge of heat-related illness symptoms index (KOSI, range [0–14]). Prevention measures currently implemented by coaches were analyzed in terms of relative compliance with specified recommendations (heat prevention score (HPS), range [0–100]).ResultsThe KOSI averaged 10.31 ± 1.81 and pointed to clear knowledge deficits: the lowest score values were shown by coaches in skiing (9.85 ± 1.80), soccer (10.07 ± 2.33) and golf (10.09 ± 1.75; pANOVA = 0.015). Heat protection in training was also deficient: The HPS showed a mean value of 62.41 ± 14.89. The greatest deficits existed in tennis (57.71 ± 14.29), mountain sports (58.17 ± 13.08) and soccer (58.70 ± 13.86; pANOVA < 0.001). No correlation between theoretical knowledge and practical prevention was found.ConclusionIn Germany, coaches are insufficiently prepared for the health hazards of heat. Promoting onsite educational programs seems essential to ensure safer sports environments.